Case report of a dentigerous cyst with mucous prosoplasia: As an incidental finding - Nimoshini Gowrinathan; C Hima Bindu Reddy; Z H Husna Sofia; R Jemima; Jeslyn Jeromy; N Vaishnavi Dhanvantri (Wolters Kluwer Medknow Publications, 2020)
Dentigerous cysts, also called follicular cysts, are developmental odontogenic cysts that occur in association with an unerupted tooth. Fluid accumulation between the enamel epithelium and enamel causes the dental follicle to separate from the crown, giving rise to such cysts. Usually, these cysts do not show any symptoms and are diagnosed during routine radiological examination. Mucous cell prosoplasia is a rare type of entity commonly seen in oral pathologies such as odontogenic cysts and might lead to diagnostic difficulties. Although mucous cell prosoplasia is considered as a harmless condition, some studies have suggested that it may be a maiden step toward malignant transformation. We report a case of the dentigerous cyst with mucous prosoplasia that presented as an incidental finding emphasizing the importance of radiographs and histopathology in the definitive diagnosis of such cases.